Effect of Progressive Muscle Relaxation Technique on Fatigue inPatients Undergoing Hemodialysis - Mehdi Bassiri moghadam; SHirin Madadkar dehkordi; Ali Mohammadpour; Amir abas Vaezi (Zanjan University of Medical Sciences and Health Services, 2014)
Background and Objectives: Fatigue is a common complaint among patients who undergo hemodialysis. Fatigue influences their somatic, mental, sentimental and cognitive states. This study aimed to determine the effect of progressive muscle relaxation technique on fatigue among patients treated with hemodialysis. Materials and Methods: In this clinical trial, 90 patients undergoing hemodialysis were recruited from two hemodialysis centers in Gonabad and Yazd and were randomly allocated into control (n=45) and trial (n=45) groups. The progressive muscle relaxation technique was presented to the trial group during three sessions. The patients were asked to make calm once a day for six weeks and at the end complete the relaxtion form. No trainings were provided for the control group patients. The intensity of fatigue was compared between the two groups. Data were collected using a questionnaire including demographic specifications, tools for assessing the severity of fatigue and self-reported checklists. Data was analyzed using the statistical methods in the SPSS. Results: The results showed no significant differences in the level of fatigue between the two groups before the intervention (p=0.12). There was significant difference in level of fatigue between the two groups after the intervention (p<0.001). Conclusion: Using the progressive muscle relaxation technique is recommended for patients of the hemodialysis wards.